SUBSTRATOS ALTERNATIVOS DO XAXIM: CULTIVO DE Laelia PURPURATA lindl. EM CASCALHO GRANÃTICO E EM MISTURA COM XAXIM - Sakane, Maria; Gil, Valdir L.; Pino, Francisco Alberto (REVISTA DE AGRICULTURA, 2015)
SUBSTRATOS ALTERNATIVOS DO XAXIM: CULTIVO DE Laelia PURPURATA lindl. EM CASCALHO GRANÃTICO E EM MISTURA COM XAXIM